Islamic Communication Strategies in the Development of Congregation-Friendly Mosques with Digital Services in the Era of Media Transformation - Katni Katni; Rido Kurnianto; Syamsul Arifin (Universitas Darussalam Gontor, 2026)
Mosques are important institutions in Islamic society, not only serving as places of worship, but also ascenters of social and educational activities. However, many mosques still face problems in providing optimalservices to the congregation. The objectives of this study are: to analyze effective Islamic communicationstrategies in increasing congregational satisfaction through digital services in mosques; to evaluate the impact of digital service implementation on congregational participation in mosque activities and other religiousactivities; and to identify factors that influence the successful implementation of congregation-friendly anddigitally serviced mosques in the context of Islamic communication in the digital era. This study uses qualitativemethods to gather in-depth information about congregation-friendly and digitally serviced mosques at theBaitul Muhlisin Mosque and the Nurul Hasan Mosque in Ponorogo. Data were collected through observation,in-depth interviews, and analysis of related documents. Data analysis uses descriptive analysis techniques toobtain a clear picture of the phenomenon under study. This study shows that the implementation of digitalservices at the Nurul Hasan Mosque in Ponorogo and the Baitul Muhlisin Mosque in Ponorogo can increasecongregational satisfaction and participation in mosque activities. Effective Islamic communication strategiesand supporting factors such as mosque management leadership, financial and resource support, activecongregational participation, and collaboration with other parties influence the successful implementation ofcongregation-friendly mosques and digital services. The results of this study indicate that mosques can becomedynamic and effective centers of religious and social activities in improving the quality of life of congregationsand the surrounding community through the implementation of appropriate digital services. Keywords: Congregation-Friendly Mosque; Digital Services; Islamic Communication